A General Review of the Draft Second Five Year Plan of Vindhya Pradesh - Planning Commission (Planning Commission, 1955)
Vindhya Pradesh was formed in 1948 by the Union of 35 States of Baghelkhand and Bundelkhand as Part, "B" State It became a Part C State, from 26th January 1950 under the Constitution of India From March 1952 it has a legislature and an elected Ministry, under a Lieutenant Governor. This rather unsettled political life of the Pradesh delayed the reorganisation of the administration and the services the reorganisation was completed finally during 1954-55. Vindhya Pradesh was amongst, the underdeveloped States of the Indian- Union. Its constituent, units some, of them so small as five square miles in area with one thousand or fifteen hundred souls, were merely sufficient to maintain the princely establishment. There were only four States whose area exceeded 1000 square miles. In 1950 the total mileage of Railway line was and still is 287 only. Metalled and fairweather roads covered 1296 and 1.075 miles respectively.
A General Review of the Draft Second Five Year Plan of Vindhya Pradesh
Government of Vindhya Pradesh